Exhumation history of the Sanshandao Au deposit, Jiaodong: constraints from structural analysis and (U-Th)/He thermochronology - Liu, X.; Fan, H.; Evans, Noreen; Yang, K.; Danisik, Martin; McInnes, Brent; Qin, K.; Yu, X. (Nature Publishing Group, 2017)
The Sanshandao gold deposit contains an estimated Au resource of > 1500 tons, however little is known about the history of exhumation, and the magnitude of displacement on the ore-hosting fault. Structural measurement revealed two phases of normal and one phase of sinistral movement on the fault. Despite of intra-sample dispersions, (U-Th)/He ages from two sub-vertical profiles show decreasing trends from the surface down to -3560 m (zircon: 123 Ma to 55 Ma; apatite 103 Ma to 0.3 Ma). Over-dispersion of AHe ages likely reflects the presence of undetected inclusions. According to the age-depth pattern, we infer that the deposit underwent an early phase of rapid cooling in the late Early Cretaceous, which was followed by a short period of thermal stagnation and a revived rapid cooling between 75 Ma and 55 Ma in response to a combined effects of late normal movement and erosion. Since the Eocene, the deposit has experienced a slow monotonic cooling. Exhumation magnitude estimates suggest that the deposit have been denudated > 5.1 km. The two phases of normal displacement along the fault occurred in the late Early Cretaceous and Late Cretaceous to Paleocene, leading to a total offset magnitude of 0.5–2.3 km.